THE IMPACT OF TRANSFORMATIONAL AND AUTHENTIC LEADERSHIP ON ACADEMIC SERVICE QUALITY: A CASE STUDY FROM PADANGSIDIMPUAN, INDONESIA - Muhammad Syahril Harahap; Sri Milfayetty; Mariani; Febriani Hastini Nasution (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the influence of transformational-authentic leadership on academic service quality in higher education institutions. Integrating the theoretical frameworks of transformational and authentic leadership, this research explores how ethical vision-driven leadership affects dimensions of academic services, particularly from the perspective of staff and faculty. Using a quantitative approach with 250 respondents across three universities in Padangsidimpuan City, North Sumatra, Indonesia data were analyzed using SPSS with descriptive and inferential statistical techniques. Results show that transformational-authentic leadership positively and significantly predicts academic service quality, with authentic relational transparency and authentic individualized consideration emerging as key contributors. The study contributes to leadership and service quality literature by proposing a hybrid leadership model as a strategic lever to elevate institutional service performance.